2017
DOI: 10.5127/jep.056316
|View full text |Cite
|
Sign up to set email alerts
|

The Subjective-Objective Disjunction in Psychometrically-Defined Schizotypy: What it is and Why it is Important?

Abstract: An interesting set of findings has emerged from the literature regarding schizotypy. Individuals with psychometric schizotypy self-report pathology in certain neuropsychological, affective experiential, expressive and olfactory abilities and subjective quality of life at levels between one and two standard deviations more severe than their non-schizotypal peers; a level often similar to that seen in chronic schizophrenia. Objectively however, individuals with psychometric schizotypy do not show concomitant imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 104 publications
(139 reference statements)
1
10
0
Order By: Relevance
“…Using a measure of implicit affect, we found that individuals with elevated levels of SocAnh showed medium-to-large decrements in implicit positive affect compared to the Control and PerMag groups. Thus, current results suggest that the finding of decreased positive affect in SocAnh is not limited to explicit measures of positive affect (Cohen et al, 2017; Li et al, 2019). Overall, the findings of the medium-to-large differences in both implicit and explicit affect in SocAnh suggest that a defining feature of SocAnh is decreased positive affect.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Using a measure of implicit affect, we found that individuals with elevated levels of SocAnh showed medium-to-large decrements in implicit positive affect compared to the Control and PerMag groups. Thus, current results suggest that the finding of decreased positive affect in SocAnh is not limited to explicit measures of positive affect (Cohen et al, 2017; Li et al, 2019). Overall, the findings of the medium-to-large differences in both implicit and explicit affect in SocAnh suggest that a defining feature of SocAnh is decreased positive affect.…”
Section: Discussionmentioning
confidence: 52%
“…Tallent and Gooding (1999), Gooding et al (2006), and Ettinger et al (2015) for a review]. It has been argued that this also calls into question the nature of any decreased positive affect on explicit measures (e.g., self-report assessments that directly ask participants questions regarding their subjective emotional experiences; Cohen et al, 2017). Given this, it is possible that decreased positive affect in SocAnh might only be found in explicit ratings of positive affect.…”
Section: Introductionmentioning
confidence: 99%
“…Such paradox could be observed in many functional domains, for instance, in neuropsychological functions and affective experience. Specifically, individuals with high schizotypal traits exaggerate the extent of their subjective concerns which is far greater than the level of objective measures 42 . Li et al 43 adopted a multidimensional approach to reveal that the deficit paradox not only exists in basic affective process, but also in emotion regulation.…”
Section: Discussionmentioning
confidence: 95%
“…The previous studies found that the schizophrenia spectrum disorder is along with subjective-objective disjunction refering to a paradoxical pattern between subjective reports and objective measures 42 . Such paradox could be observed in many functional domains, for instance, in neuropsychological functions and affective experience.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation